O cemitério dos vivos: a experiência manicomial de Lima Barreto - Barros, Adeliana Alves (2016)
The starting point of this investigation is the asylum experience of writer Lima Barreto, admitted as a psychiatric patient in 1914 and 1919, to the Hospício Nacional de Alienados do Rio de Janeiro. From the writer’s analysis of the “asylum spectacle”, described as “a place that sentences to social death”, that appears on Diário do Hospício and O Cemitério dos Vivos, this paper reviews the beginning of psychic science and its assumptions originated mostly from Europe and performed in Brazil, presuming madness as an inseparable medical and social problematic. An analysis will be made based on the “self-writing” of Lima Barreto, from the documents produced by the institution responsible for this admission (medical charts) and the works toward thinking psychiatry and madness as a mental disease. The asylum experience from the insane himself, the history of psychiatry theories that defined and legitimated what were normal and pathological, the classification and creation of the medical institutional space, the routine of the asylum and the medical specialization towards healing insanity. From those resources, was considered the imposition of a power relation between the doctor and the sick individual, the practices around the “insane”, the confiscation of “madness” through the physician’s specialist point of view, and the subjects that were part of the psychiatry theory research, exposed to their therapy and practices, that, in most part, were poor, black and handymen, from a perspective that comprehends an eminently social topic, although elaborated as a disease.